The origin of the general part of the bürgerliches gesetzbuch - Mendoza del Maestro, Gilberto (2018)
In this article, the author develops a historical analysis of the General Section of the Bürgerliches Gesetzbuch, making important comments on the social and political context in which it was written. Additionally, this analysis presents a review of its process of production, inside the work of the commissions and preliminary texts.This is dealt by presenting some of the sharpest criticism made to the codification efforts and the academic debate on the importance of having a General Section or even a code for the German area. Finally, the author sets the relationship between this German product and other laws that appeared in countries influenced by it.